(untitled) (Research, Society and Development, 2019)
The objective of this study is to analyze the impact of racial quotas as affirmative actions for access to higher education. This is an article of analysis, and to meet the objective it was necessary to weave brief concepts about racial inequality in Brazil; understand conceptually affirmative actions and racial quotas; examine your legal support. `a qualitative and bibliographical study that started from the premise of the lass struggle established in society throughout history, as well as racial inequality and violence against blacks in Brazil. The study found that the quota system was a watershed in the democratization of black access to higher education, albeit with contrary arguments and allegations that quotas discriminate and instill the idea that blacks would be incompetent. It also noted the high number of students evading the University, and the urgency of affirmative action policies aimed at the permanence of these students in the Univers.